PERAN SUPERVISI PENGAWAS SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN - Yeni Rosnasari; Lilis Kholisoh; Asep Saepul Hidayat; Awang Kustiawan (LPPM Universitas Cipta Mandiri, 2025)
This study focuses on the problem of the role of school supervisor supervision in improving the quality of learning, which is based on the problem of several obstacles faced by teachers in efforts to improve the quality of learning. This study uses a descriptive method and a qualitative approach. Based on the study, the following conclusions were drawn: (1) Problems regarding the quality of learning are based on the low efforts and creativity of teachers in overcoming the weaknesses of external aspects of teacher personnel; (2) The role of supervisor supervision in improving the quality of learning is essentially the role of supervisors in fostering, guiding, directing, controlling, assisting, cooperating in the process of overcoming several obstacles faced, as well as efforts to innovate and develop towards a more effective and productive direction; (3) Development of the role of supervisor supervision in improving the quality of learning, like development in efforts: (1) building learning strategies that are in accordance with needs and conditions; (2) assisting teachers in building innovation strategies in learning; (3) supporting and facilitating the development of learning through the use of ICT media; (4) building learning models through the application of information system management; (5) building learning models in accordance with the development of science and technology, and others.